Sarkisian, Aram G. 2025. Orthodoxy on the Line: Russian Orthodox Christians and Labor Migration in the Progressive Era. New York: New York University Press, 336 pp - Moulton, Gavin (Rocznik Ruskiej Bursy, 2026)
Forthcoming.